PROMOTING THE DEVELOPMENT OF LEARNERS’ TRADITIONAL LITERACIES THROUGH DIGITAL STORYTELLING - Syam, Andi Tenrisanna (LLT Journal: A Journal on Language and Language Teaching, 2022)
Learners frequently have problems comprehend the texts and arrange sentences to become good paragraphs. To address this issue, digital storytelling may be utilized as a technique to aid learners' reading and writing skill. The author aimed at finding out whether or not digital storytelling increases the learners’ reading and writing skills. The author employed a quasi-experimental design. The 80 learners of sharia banking study program at IAIN Palopo participated in this research. The instruments of this research were reading tests and writing essays. Reading test consisted of 30 numbers; meanwhile writing test consisted of one number. The test had two parts: an initial test and a final test. To measure the significance difference on the learners’ achievement in the two-class, the average, standard deviation, and t-test was computed. A significant difference was found when the two means were compared (82.50 57.05); the experimental class average improved after the treatment was implemented. Nevertheless, the learners in control class showed no improvement. Prior to the treatment, the learners in both classes exhibited equivalent writing skill. On the other hand, they had different achievement after being treated. Furthermore, whereas the experimental class experienced a change, the control class did not. Then, the author asserted that digital storytelling can increase the learners’ reading and writing skills. The author hopes findings of this research can be valuable resources for the learners, the lecturers, and the future researchers.